Acetic acid hydrodeoxygenation on molybdenum carbide catalysts. Issue 11 (22nd May 2018) - Kumar, Anurag; Phadke, Sohan; Bhan, Aditya
Abstract : Kinetics and site requirements of acetic acid hydrodeoxygenation on molybdenum carbide – a stable and selective catalyst under atmospheric hydrogen pressure. Abstract : As-synthesized molybdenum carbide shows >98% selectivity (deoxygenated products) and stable chemical conversion for >30 h time-on-stream after an initial deactivation period of ∼9 h for vapor phase hydrodeoxygenation of acetic acid at a low temperature (403 K) and atmospheric pressure. Space–time variation studies show acetaldehyde as a primary unstable product, ethanol as a secondary unstable product, and ethyl acetate and ethylene as secondary stable products suggesting a sequential reaction pathway for acetic acid deoxygenation on Mo2 C. The concurrent half and zero-order dependence of acetic acid HDO rates on H2 and acetic acid pressure, respectively, suggests that catalytic sites for H2 activation are distinct from those required for the activation of acetic acid consistent with prior reports for deoxygenation of aromatic ethers and alcohols. Catalyst surface evolution by oxygen (O : Mobulk ∼ 0.3) and carbon (C : Mobulk ∼ 0.1) deposition from the reactant oxygenate was noted using temperature programmed surface reaction (TPSR) with hydrogen post reaction. Higher O*/Mo deposition with acetic acid in reference to H2 O, CO2, and aromatic ethers at similar oxygenate pressures suggests that the identity of the oxygenate determines its proficiency for heteroatom deposition on fresh carbidic materials. Catalytic site densities were estimated via in situ titration using 2, 2-dimethylpropanoic acid (DMPA) as a reagent to calculate a turnover frequency (TOF) of (9 ± 1) × 10 −4 mol s −1 molDMPA −1 . The X-ray diffraction patterns and X-ray photoelectron spectra of passivated Mo2 C catalyst samples before and after acetic acid reaction indicate the presence of a carbide/oxycarbide phase, even though the bulk structure of orthorhombic β-Mo2 C is retained.